Fluid flow past vertical tubes - 282426 Tang, Chee Hwee (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering (Production)) - Universiti Teknologi Malaysia, 1999